2020
DOI: 10.4103/jcd.jcd_610_20
|View full text |Cite
|
Sign up to set email alerts
|

To compare and evaluate the antimicrobial activity of three different root canal sealers: An In Vitro Study

Abstract: Aim of the Study: The purpose of this study is to compare and analyze the antimicrobial activity of three different root canal sealers. Materials and Methods: In this study, the antimicrobial activity of three different root canal sealers were compared against two strains of bacteria Enterococcus faecalis which is known to be common isolates of necrotic pulp and endodontic lesions. This test was done at various time intervals (1, 6, 15, and 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In one day and one weeks bioceramic sealer act in a better way, which may be due to the sealer containing an amount of oxide compounds that potentially have antimicrobial activity These findings are consistent with previous researches conducted on bioceramic sealers have significant antibacterial efficacy against E. faecalis up to one week (19,26,28,29) Also in another study, Mangat et al(29) compared the antimicrobial activity of Bioceramic BC sealer and MTA fillapex sealer against E. faecalis at distinct time intervals from 1day to 1 week and concluded that Bioceramic sealer showed better antimicrobial activity than MTA Fillapex and Apexit in both (ADT) and (DCT). In another word was implemented and Figure 2 depicts the antimicrobial activity of tested endodontic sealers made from a modified direct contact test.…”
Section: Direct Contact Testsupporting
confidence: 91%
“…In one day and one weeks bioceramic sealer act in a better way, which may be due to the sealer containing an amount of oxide compounds that potentially have antimicrobial activity These findings are consistent with previous researches conducted on bioceramic sealers have significant antibacterial efficacy against E. faecalis up to one week (19,26,28,29) Also in another study, Mangat et al(29) compared the antimicrobial activity of Bioceramic BC sealer and MTA fillapex sealer against E. faecalis at distinct time intervals from 1day to 1 week and concluded that Bioceramic sealer showed better antimicrobial activity than MTA Fillapex and Apexit in both (ADT) and (DCT). In another word was implemented and Figure 2 depicts the antimicrobial activity of tested endodontic sealers made from a modified direct contact test.…”
Section: Direct Contact Testsupporting
confidence: 91%
“…[ 19 ] If RJ can effectively eliminate E. faecalis at a concentration of 10 mg/ml, it may hold promise as an adjunctive treatment in cases of persistent endodontic infections where E. faecalis is implicated. In the field of endodontics, where infections can involve various microorganisms,[ 20 21 ] having an antimicrobial agent effective against both bacteria and fungi such as C. albicans is highly advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…Root canal sealers with antimicrobial activity can help improve the success rate of endodontic treatment and are especially advantageous in clinical situations where there is a persistent or recurrent infection. [ 9 10 11 ]…”
Section: Discussionmentioning
confidence: 99%